The Importance of Happiness and Its Relevance (International Journal of Innovative Research in Computer Science & Technology, 2020)
There has been a lot of interest in  fulfillment all through the most recent decade filled by  improvements in neuroscience and the evaluation of joy.  Positive frontal cortex science has arisen as an obvious  solicitation inside the canny neighborhood give a home to  the divulgences of the new astute assessment of  satisfaction. In 2011, positive frontal cortex research was  the most standard course at Harvard College and in that  very year Harvard was arranged as the top school on the  planet by the UK's Times Higher Education Supplement.  There may be no causal connection between these two  contemplates yet certainly zeroing in on the shrewd  examination on satisfaction isn't an obstacle to institutional  achievement. What is going on with the new keen  examination on satisfaction and what, hoping to be any, is  its importance to Higher Education? This is the solicitation  that this paper will research and endeavor to reply.
Keywords: Curriculum Design; Happiness Studies; Positive Psychology; Undergraduate Education